2019
DOI: 10.3390/molecules24173125
|View full text |Cite
|
Sign up to set email alerts
|

Tracing Potential Covalent Inhibitors of an E3 Ubiquitin Ligase through Target-Focused Modelling

Abstract: The Nedd4-1 E3 Ubiquitin ligase has been implicated in multiple disease conditions due its overexpression. Although the enzyme may be targeted both covalently and non-covalently, minimal studies provide effective inhibitors against it. Recently, research has focused on covalent inhibitors based on their characteristic, highly-selective warheads and ability to prevent drug resistance. This prompted us to screen for new covalent inhibitors of Nedd4-1 using a combination of computational approaches. However, this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 32 publications
1
5
0
Order By: Relevance
“…The catalytic SER124 is in-between the a 3 -helix and the b 5 -strand in the active site. The approach of irreversible covalent inhibition of biological targets using covalent compounds to cure pathogenic diseases has remained promising in the drug design area (Bjij et al, 2019), and the dynamic perspectives in this study corroborated with the experimental protocol reported on the putative covalent inhibition of the Ag85C role through the interaction of SER124 residue with the phosphorus oxygen atom of the Cis (b-isomer)monocyclic enolphosphorus Cycliphostin (CyC 8b ) compounds.…”
Section: Stability and Fluctuation Patterns Of Ag85c Systemssupporting
confidence: 80%
“…The catalytic SER124 is in-between the a 3 -helix and the b 5 -strand in the active site. The approach of irreversible covalent inhibition of biological targets using covalent compounds to cure pathogenic diseases has remained promising in the drug design area (Bjij et al, 2019), and the dynamic perspectives in this study corroborated with the experimental protocol reported on the putative covalent inhibition of the Ag85C role through the interaction of SER124 residue with the phosphorus oxygen atom of the Cis (b-isomer)monocyclic enolphosphorus Cycliphostin (CyC 8b ) compounds.…”
Section: Stability and Fluctuation Patterns Of Ag85c Systemssupporting
confidence: 80%
“…Aided by recent advancements in structural biology and chemistry, covalent inhibitors have emerged as a potentially effective approach towards PPI inhibition [37,38]. Studies have indicated that covalent drugs are less likely to promote resistance [39], which could be important for diseases such as cancer and infectious diseases where drug resistance is a major challenge. Covalent inhibitors are generally comprised of a specificity group to recognize the target protein and a functional "warhead" that forms a covalent linkage with the protein.…”
Section: Introductionmentioning
confidence: 99%
“…Although significant efforts have been made to aid the modelling and design of noncovalent peptides, the molecular simulations of covalent peptide interactions remain a challenging task, especially with the lack of peptide-specific validated protocol that takes into account covalent binding between the peptide and the receptor [18,[20][21][22] . Along with our earlier reports on covalent docking [23][24][25][26][27][28][29] , The current report will concentrate on covalent peptide docking, its challenges, and provide potential solutions including technical guidance to useful tools and approaches to assist with the rational design of covalent peptide inhibitors.…”
Section: Small Molecules Inhibitors Vs Peptides -Evolution Of Covalen...mentioning
confidence: 99%
“…We have previously discussed covalent docking in detail, including its uses and applications, available tools, advantages and disadvantages [25][26][27] . To avoid repetition of information, the primary objective of this review is the covalent docking technique specifically related to peptidebased molecules.…”
Section: Covalent Docking Of Peptides In Drug Discovery -Not Trivial!mentioning
confidence: 99%